Predominance of Antibiotic-Resistant Bacteria in Recurrent Tonsillitis and the Frequency of Antibiotics: A Clinical Study: Dominasi Bakteri yang Kebal Antibiotik pada Tonsilitis Kambuhan dan Frekuensi Antibiotik: Sebuah Studi Klinis - Fliafel, Intisar Khlaif; Obayes, Maryam Sadiq; Saleem, Hanan Kareem (Universitas Muhammadiyah Sidoarjo, 2024)
Background; Antibiotic resistance in bacteria has become a significant concern in the treatment of recurrent tonsillitis, with increased resistance potentially complicating management strategies. Aims of the study; Evaluate the predominance of antibiotic-resistant bacteria in recurrent tonsillitis cases and to assess the frequency and patterns of antibiotic use among affected patients, in order to inform better treatment strategies and combat resistance. Methodology; This clinical study, conducted at Al-Habbobi Teaching Hospital over six months, involved 500 patients with recurrent tonsillitis. Data on sociodemographic factors, medical history, and antibiotic usage was collected. Throat swabs were cultured, and bacterial identification was performed. Antibiotic resistance was tested using the Kirby-Bauer disk diffusion method, with informed consent obtained. Result; The results showed that 52% of participants were male and 48% female, with the highest age group being 6-8 years (40%). Regarding socioeconomic status, 50% were in the middle group. Antibiotic usage was 45% for amoxicillin, 30% for azithromycin, and 15% for clindamycin, all showing significant relationships (p<0.05). Streptococcus pyogenes was the most isolated bacteria (40%), with significant associations with antibiotic use. Antibiotic resistance was highest in Streptococcus pyogenes (60%) and Staphylococcus aureus (50%). Pain severity showed 60% with severe pain, with 30% experiencing recurrence, both with significant p-values (p<0.05). Conclusions; The study highlights the high prevalence of antibiotic-resistant bacteria, particularly Streptococcus pyogenes. The significant correlation between pain severity, recurrence, and antibiotic resistance suggests that improper antibiotic use may contribute to resistance, emphasizing the need for targeted treatments and antibiotic stewardship. Highlights: Antibiotic resistance complicates recurrent tonsillitis treatment strategies. Assess antibiotic-resistant bacteria prevalence and usage patterns in tonsillitis. Targeted treatments, stewardship crucial against Streptococcus pyogenes resistance. Keywords: Antibiotic resistance, Recurrent tonsillitis, Streptococcus pyogenes, Pain severity, Antibiotic usage, Recurrence rate